Spatial Distribution and Accessibility Analysis of Mosques in Bogor City Using GIS-Based Buffer Zone Analysis - Rina Trisminingsih; Muhammad Faiz (JUSIFO : Jurnal Sistem Informasi, 2026)
Mosque development in rapidly urbanizing areas is often driven by local initiatives, creating potential disparities in spatial distribution and accessibility. This study aims to develop a WebGIS-based framework to analyze the spatial distribution of mosques and assess their potential service coverage in Bogor City, Indonesia. A total of 785 mosque records from Sistem Informasi Masjid were integrated with district-level population data and administrative boundaries. Variable-radius buffers were generated from population density and mosque congregation capacity, while the WebGIS platform supported interactive filtering, visualization, and spatial exploration. The analysis revealed contrasting patterns: selected locations in Bogor Selatan exhibited greater buffer overlap and a relatively concentrated arrangement, whereas Bogor Barat showed a more dispersed pattern. Preliminary verification classified seven of ten georeferenced records as appropriate. However, because mosque locations were generated through city-name georeferencing rather than verified coordinates, the findings should be interpreted as exploratory. The proposed framework therefore serves as a preliminary tool for visualizing mosque distribution and potential service coverage at the city level.